Generation Y in Turbulence of Conflict Resolution and Peace of Religious People in Palembang - Hamidah; Ismail, Nawari (International Journal of Psychosocial Rehabilitation, 2020)
— This article aimed to find strategies to develop the role of the generation Y in the peaceful conflict resolution of religious communities in Palembang. The three main focus in this research are: (1) describe religiosity of generation Y, (2) socio-cultural and psychological capital of the generation Y in the peaceful conflict resolution of religious community, (3) a strategy to develop the role of the Y generation in the peaceful conflict resolution of religious communities. The research method is mix method with questionnaire data collection techniques, in-depth interviews, documentation. Data will be analyzed statistically simple and inference, as well as thick description. The novelty from this study is alternative actors who have actually been influential in the process of peaceful conflict resolution that have not been much studied are the Y generation who are very close to information technology or social media; research related to the resolution of peaceful conflicts and community resilience in Indonesia, so far has not been much studied and linked with ’generation theory’, especially from the generation Y.